The Processes of Creation and Co-Creation in Painting and Icon Painting - Yakovleva, Nonna A. (Actual Problems of Theory and History of Art, 2017)
The door to the renaissance of icon-painting can hardly be opened without a balanced combination of two research methods, i.e. theological and art historical approach. Crucial tasks include studying the specifics of an iconic image in comparison with an artistic one.Treated as artifacts, both a painting and an icon are the mixture of the ideal and the material where a material component carries an ideal image. Speaking of painting:— the artistic image enjoys the dynamic integrity and subjectivity: it originates in the artist’s superconscious, penetrates with his or her consciousness in the form of a conception and evolves (P. V. Simonov, A. A. Mikhailova) within the creative process to become a unique artistic image coded in the material;— the artistic image fixed in the finished work of art (painting) also exists as an objective, “second” reality enshrining additional (extra) knowledge of the world, with this knowledge being generated in the evolution of the form of meaning construction;— as soon as the artistic image transforms into a perceived image in the process of active co-creative perception, it regains its subjectivity. The processes of creation and co-creation in the artistic image dynamics are symmetrical but not similar. Although determined by external factors to some extent, the process of creation is mainly driven by the author’s artistic will, while the process of co-creation depends directly on the author’s artistic image, i.e. it is guided by the author’s artistic will. From the functional perspective, the prevailing function of the artistic image is to regenerate into perceived artistic image which would serve the goals dictated by the time and society. According to the Holy Tradition, icon painting is rooted in the acheiropaeic images of Christ and the Holy Mother of God as well as the images made by Luca, a doctor and an artist, during Her lifetime and consecrated by Her Word. These are the higher forces that give the image the revitalizing power and make it an icon, i.e. a holy image.